1985
DOI: 10.1007/978-1-4613-8548-6
|View full text |Cite
|
Sign up to set email alerts
|

Arithmetic Functions and Integer Products

Abstract: Arithmetic functions and integer products. (Grundlehren der mathematischen Wissenschaften ; 272) Bibliography: p. Includes index. 1. Arithmetic functions. I. Title. II. Series. QA246.E55 1984 With 2 Illustrations. 2. Numbers, Natural.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
53
0
3

Year Published

1987
1987
2012
2012

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 0 publications
6
53
0
3
Order By: Relevance
“…Furthermore, y 3 = x 3 , for otherwise we obtain the equality (2ak + 1)(α + y 4 ) = α + x 4 , which is impossible as α / ∈ Q. Similarly, 4 is not a permutation of y 1 , y 2 , y 3 , y 4 , which is the desired conclusion.…”
Section: Proofsmentioning
confidence: 81%
“…Furthermore, y 3 = x 3 , for otherwise we obtain the equality (2ak + 1)(α + y 4 ) = α + x 4 , which is impossible as α / ∈ Q. Similarly, 4 is not a permutation of y 1 , y 2 , y 3 , y 4 , which is the desired conclusion.…”
Section: Proofsmentioning
confidence: 81%
“…There is a well-developed theory with many general results about the existence of means of arithmetic functions, see Elliott (1985); Indlekofer (1980Indlekofer ( , 1981Postnikov (1988). However, those general results do not imply the specific statements of this work.…”
mentioning
confidence: 83%
“…More recently, Bombieri, Friedlander and Iwaniec [2] (see also [1]), using an idea of Motohashi [9], gave a very general Bombieri-Vinogradov type theorem for functions / that can be represented as convolutions of "well-behaved" functions. Elliott [3,Chapter 7] [4] and the author [8] showed that all additive functions satisfy a Bombieri-Vinogradov type theorem.…”
Section: ■* (Aq)=\mentioning
confidence: 99%